Crazy mountain kiss [large type] : a Sean Stranahan mystery - McCafferty, Keith (McCafferty, Keith. Sean Stranahan mystery., 2015)
It's April, but there's still snow on the Montana mountains the day a fisherman sees a Santa hat in the chimney of his rented cabin and finds the body of a teenage girl wedged into the chimney. When Sheriff Martha Ettinger and her team arrive, they identify the body as a promising young rodeo star missing since November.